UTILIZING JIGSAW METHOD TO IMPROVE LEARNING ACTIVITIES AND STUDENTS’ HISTORY LEARNING OUTCOME AT CLASS XII IPS (SOCIAL SCIENCE) OF SMA NEGERI 10 PEKANBARU - Julita Marta; Raja Usman (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
The purpose of this study was to improve the activities and learning outcomes in two cycles. An initial test was conducted before carrying out the learning process. The score in the pre-cycle was 2390; the score in cycle I was 2885, and the score in cycle II was 3070. Meanwhile, the average score in th pre-cycle was 68.29, in cycle I, it increased to 78.92 and cycle II, it increased to 87.71. The score was obtained based on minimum learning mastery (KKM) which was 80. In the pre-cycle, there were only 8 students (22.86%) who reached the KKM while 27 students did not reach the KKM (77.14%). In cycle 1, 24 students (68.57%) reached the KKM and 11 students did not reach the KKM (31.43%). Moreover, in cycle II, 34 students reached the KKM (97.14%) and only 02.86% of students did not reach the KKM. From these results, the highest score in pre-cycle was 85 and the lowest score was 45; the highest score in cycle I was 95 and the lowest score was 75. In addition, based on the range and criteria of the score, the percentage in pre-cycle was 3143% (enough), in cycle I was 37.14% (very high), and in cycle II was 51.43% (very high). Then, students’ activity in each cycle increased for 71.43 and 85.71 respectively. It could be concluded that jigsaw method improved the learning activity and students’ learning outcomes at class XII IPS SMA Negeri 10 Pekanbaru.